Cars in Europe : Supply Chains and Spillovers during COVID-19 Times - Boranova, Vizhdan (IMF Working Papers; Working Paper ;, 2022)
The auto sector is macro-critical in many European countries and constitutes one of the main supply chains in the region. Using a multi-sector and multi-country general equilibrium model, this paper presents a quantitative assessment of the impact of global pandemic-induced labor supply shocks-both directly and via supply chains-during the initial phase of the COVID-19 pandemic on the auto sector and aggregate activity in Europe. Our results suggest that these labor supply shocks would have a significant adverse impact on the major auto producers in Europe, with one-third of the decline in the value added of the car sector attributable to spillovers via supply chains within and across borders. Within borders, the pandemic-induced labor supply shocks in the services sector have a bigger adverse impact, reflecting their larger size and associated demand effects. Across borders, spillovers from the pandemic-induced labor supply shocks that originate in other European countries are larger than those that originate outside the region, though the latter are still sizable.